Perceived Barriers to Weight Loss among Hispanic Patients with Non-alcoholic Fatty Liver Disease. (September 2022) - Heredia, Natalia I.; Thrift, Aaron P.; Balakrishnan, Maya
Introduction: Non-alcoholic fatty liver disease (NAFLD) is a growing problem in the United States and Hispanics experience the highest burden of this disease. Weight loss, physical activity (PA) and a healthy diet are the mainstay for NAFLD treatment, but patients experience barriers to behavior change. The purpose of this study was to identify barriers hindering Hispanic patients with NAFLD from making changes to PA and dietary habits. Methods: Participants referred to a multidisciplinary clinic completed self-administered questionnaires that measured barriers to greater PA engagement and eating healthier, with both close-ended and open-ended responses. One bilingual coder reviewed and categorized all open-ended responses. Results: The study population included 414 patients. The top five barriers for eating healthier were cost, perceptions that healthier food does not taste good, lack of time to cook, difficulty of cooking, and difficulty in going to the grocery store. Lack of time, feeling lazy, pain, a lack of place to exercise, and the perception that exercise is difficult were the top five barriers to PA engagement. Conclusions: Since Hispanic adults with NAFLD experience similar barriers to Hispanic adults more generally, existing behavioral lifestyle interventions may work well in this clinical population with some adaption for NAFLD-specific education.